Gambaran kejadian karies gigi molar pertama permanen dan tingkat pengetahuan tentang kesehatan gigi pada anak usia 9-12 tahun di SD Negeri 4 Sanur Denpasar - I Wayan Gita Pratama; Mia Ayustina Prasetya; Ketut Suarjana (Bali Dental Journal, 2019)
Introduction: Dental caries is a disease caused by multifactorial, one of which is a factor in behavior or attitude of oral hygiene. This is caused by to lack of knowledge about maintain oral hygiene. The purpose of this study is to describe the incidence of dental caries of permanent first molar basis of age, gender, behavior and knowledge levels in children aged 9-12 years in SD Negeri 4 Sanur Denpasar. Method: Descriptive study used with cross sectional study with 107 student in SD Negeri 4 Sanur as the sample, the samples was obtained by systematic random sampling. Result: This study shows the prevalence of caries in SD 4 Sanur Denpasar amounted to 52.3%. The prevalence of dental caries in respondents who had a poor behavior of 77.6%. There is a significant associated between the prevalence of caries by the behavior of maintain oral health (p=0.000). While the prevalence of caries based knowledge tends to occur in respondents who have less knowledge both in the amount of 100% and there is a significant associated between dental caries based knowledge to maintain oral health (p=0.003). Conclusion: Based on these results the incidence of caries in SD 4 Sanur Denpasar relatively high. Student in SD 4 Sanur Denpasar mostly caries have poor healthy behavior and have less knowledge. Public health center expected to provide counseling and common practices on how to maintain healthy teeth and mouth regularly.